Moralitas dalam Perjalanan Sejarah Islam - Imran Muhammad (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2020)
Today moral issues are still very important to campaign for, how could it not be, currently immoral behavior still occurs in this country. Efforts to resolve immoral behavior in order to form a good society. Islam teaches that goodness is expected to be able to be a solution to various problems and immoral behavior that often occurs, therefore this research aims to find out how the urgency of morality is in the course of Islamic history. The data analysis technique that the writer uses is a library analysis technique or library research. Based on the results of the analysis and research, it can be concluded that morality and Islam are two things that specifically have a relationship, because in Islam itself morality is also known as morals. The introduction of morality in the Prophet was explicitly implied when the Prophet patiently faced various trials that had been faced with the severity of the thoughts at that time.